Organizational aspects of distance learning in postgraduate training of pharmacy specialists - V. M. Tolochko; M. V. Zarichkova; I. V. Mishchenko; Y. P. Medvedyeva (Zaporozhye State Medical University, 2014)
The article is dedicated to study of organizational aspects of distance learning (DL) implementation in the postgraduate training of specialists of practical pharmacy, based at the experience of Management and Economics of Pharmacy Department of Institute of Pharmacy Specialists' Professional Development, National University of Pharmacy. The 5 main steps of implementation have been described, its content and meaning have been studied. It was accented, that it is necessary to elaborate the unified approach for calculation of educational and methodical work, its registration with the right to issue the state certificate. It was marked the readiness for practical implementation of DL on the assumption of completion of last preparatory period at the state level.